Legitimacy and innovation in social enterprises. (June 2023) - Bunduchi, Raluca; Smart, Alison U; Crisan-Mitra, Catalina; Cooper, Sarah
This article examines the interrelationship between legitimacy building efforts – the different ways in which social enterprises (SEs) conform to stakeholder expectations – and types of innovation – the different approaches by which they create social and economic value through product, process and business model innovation. Using a multi-case study research design of twenty SEs in Scotland and Romania, we find that the SEs adjusted their approach to legitimacy building depending upon the types of innovation and stakeholder involved. Also, while all SEs pursued pragmatic and moral legitimacy through conforming with their stakeholders' expectations, the type of innovation shaped the way in which they prioritised one form of legitimacy over another to deal with the tensions involved in pursuing legitimacy with heterogeneous stakeholders. This finding emphasises the importance of innovation type when explaining how SEs balance the tensions involved in trying to conform to a wide range of heterogeneous stakeholders with different expectations.